Conserved Nuclear Localization Signal in NS2 Protein of Bombyx Mori Bidensovirus: A Potential Invertebrate ssDNA Virus Trait - Qian Yu; Jiaxin Yan; Ying Chen; Jinfeng Zhang; Qi Tang; Feifei Zhu; Lindan Sun; Shangshang Ma; Xiaoyong Liu; Keping Chen; Qin Yao (Viruses)
Bombyx mori bidensovirus (BmBDV), a significant pathogen in the sericulture industry, holds a unique taxonomic position due to its distinct segmented single-stranded DNA (ssDNA) genome and the presence of a self-encoding DNA polymerase. However, the functions of viral non-structural proteins, such as NS2, remain unknown. This protein is hypothesized to play a role in viral replication and pathogenesis. To investigate its structure and function, we employed phylogenetic analysis, subcellular localization, mutational analysis, and a dual-luciferase reporter system to characterize the nuclear localization signal (NLS) within NS2 and its effect on viral promoter activity. Additionally, co-immunoprecipitation and mass spectrometry were utilized to identify host proteins interacting with NS2. We identified a functional bipartite NLS in NS2, validated the combination pattern of key amino acids, and demonstrated its role in regulating viral promoter activity. Furthermore, we identified potential NLSs in NS2 homologs in other invertebrate ssDNA viruses based on sequence analysis. We also revealed interactions between NS2 and host nuclear transport proteins, suggesting that it plays a role in nuclear transport and viral replication. This research underscores the importance of NS2’s NLS in BmBDV’s life cycle and its potential conservation across invertebrate ssDNA viruses, providing insights into virus–host interactions and avenues for antiviral strategy development.